2016
DOI: 10.1111/ter.12197
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Cenomanian vs. Cenozoic folding in the High Atlas revealed by palaeomagnetic data

Abstract: Palaeomagnetic data, and specifically remagnetizations, are used to constrain the geometric reconstruction at 100 Ma of three anticlines cored by gabbroic intrusions and Triassic shales in the Central High Atlas, Morocco. Previous palaeomagnetic results have revealed that the Mesozoic sediments of this region acquired a pervasive remagnetization at the end of the Early Cretaceous. The restoration of palaeomagnetic vectors to the remagnetization stage (100 Ma) allows us to determine the dip of the beds during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…Therefore, the attitude of strata at the moment of the remagnetization is not necessarily horizontal, since there is a previous deformational event that conditions the geometry at the time of acquisition and its subsequent deformation due to a second tectonic event. Remagnetizations acquired before tectonic inversion of the basins but after syn‐sedimentary deformation are relatively common (Calvín, Casas‐Sainz, et al, ; Casas et al, ; Soto et al, ; Soto et al, ; Torres‐López et al, ; Villalaín et al, ) because remagnetizations occur in sedimentary basins owing to different mechanisms during burial (Aubourg et al, ; Katz et al, ; Torres‐López et al, ).…”
Section: Reconstruction Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the attitude of strata at the moment of the remagnetization is not necessarily horizontal, since there is a previous deformational event that conditions the geometry at the time of acquisition and its subsequent deformation due to a second tectonic event. Remagnetizations acquired before tectonic inversion of the basins but after syn‐sedimentary deformation are relatively common (Calvín, Casas‐Sainz, et al, ; Casas et al, ; Soto et al, ; Soto et al, ; Torres‐López et al, ; Villalaín et al, ) because remagnetizations occur in sedimentary basins owing to different mechanisms during burial (Aubourg et al, ; Katz et al, ; Torres‐López et al, ).…”
Section: Reconstruction Methodologymentioning
confidence: 99%
“…In the last years, one more step has been taken with the development of a method that allows obtaining the geometry at the age of the remagnetization (Villalaín et al, , ) from the study of syn‐folding remagnetizations. This method has been used satisfactorily in several works in the Iberian plate (Casas et al, ; Soto et al, , ) and in the Central High Atlas (Calvín, Casas‐Sainz, et al, ; Torres‐López et al, ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Ettaki et al (), Michard et al (), and Saura et al () evidenced the occurrence of an early diapirism during the Jurassic that individualized sedimentary depocenters between narrow thresholds (the present‐day ridges). By means of detailed paleomagnetic studies performed in Jurassic remagnetized limestones at the limbs of the anticlines, Torres‐López et al () demonstrated that these anticlines were already structured before the Late Cretaceous. Regarding the superposition of different sets of folds during the Cenozoic compression, Moussaid et al () showed through a paleomagnetic study that the curvature of the Aït Attab syncline is primary, probably related to the orientation of Mesozoic extensional structures.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the CHA ridges are structures inherited from the Mesozoic extensional stage, initially formed as straight, long diapirs (salt walls) and conditioned by the structural pattern of the basement (Charrière, ; Mattauer et al, ). These salt walls acted as sedimentary highs between Jurassic sedimentary depocenters (Ettaki et al, ; Saura et al, ), and some of these anticlines already presented steeply dipping limbs during the Cenomanian age (Torres‐López et al , ).…”
Section: Introductionmentioning
confidence: 99%